Разложите на множители выражения: а) (a-b)a + a(2-x) - x (2-b) б) (x-2)(x+3) + 2(x+1)
Разложите на множители выражения:
а) (a-b)a + a(2-x) - x (2-b)
б) (x-2)(x+3) + 2(x+1)
Ответ(ы) на вопрос:
1)[latex](a-b)a + a(2-x) - x (2-b)[/latex][latex]=a^{2}-ab+2a-ax-2x+xb= a^{2}-ax-b(a-x)+2(a-x)=
[/latex][latex]a(a-x)-b(a-x)+2(a-x)=(a-x)(a-b+2)[/latex]
[latex](x-2)(x+3) + 2(x+1)[/latex][latex]2)= x^{2} -2x+3x-6+2x+2= x^{2} +3x-4=(x-1)(x+4)[/latex]
[latex]D=9+16=25[/latex]
[latex]x_{1} = \frac{-3-5}{2} =-4[/latex]
[latex] x_{2} = \frac{-3+5}{2} =-1[/latex]
Не нашли ответ?
Похожие вопросы